La1−xMn1−yO3±δ buffer layers on inclined substrate deposited MgO templates for coated conductors. (29th January 2021) - Troshyn, Oleksiy; Hoffmann, Christian; Große, Veit; Hänisch, Jens; Becker, Lucas; Gross, Rudolf
Abstract: Most commercial high-temperature superconducting coated conductors based on ion beam assisted MgO deposited templates use LaMnO3 (LMO) films as the terminating buffer layer. In contrast, coated conductors based on inclined substrate deposition (ISD)-MgO technology are still produced with homoepitaxial (homoepi)-MgO as the cap layer. In this work we report on the deposition of LMO buffer layers on ISD-MgO/homoepi-MgO by electron beam physical vapor deposition. The growth parameters of textured LMO films were studied systematically and their properties were optimized regarding the critical current density ( J c ) of the subsequently deposited DyBa2 Cu3 O7− δ (DyBCO) superconducting films. LMO films without outgrowths at the surface were obtained at growth rates of up to 4 Å s −1 . Despite the formation of non-stoichiometric LMO films containing 59% La, single-phase films were obtained at substrate temperatures below 775 °C and at oxygen partial pressures of up to 4 × 10 −4 mbar due to a large homogeneity region towards La. The J c values of DyBCO films deposited on LMO were found to be independent of the LMO thickness in a range from 50 nm to 450 nm. DyBCO films on LMO reach J c = 0.83 MA cm −2 at 77 K in zero applied field. This value is up to 30% higher than those of DyBCO films grown directly on homoepi-MgO. The wide range of LMO growth parameters and higher J c values of DyBCO on LMO compared to DyBCO on homoepi-MgO make this material attractive for its use in manufacturing coated conductors based on ISD-MgO technology.